Številčni razvoj prekmurskih Madžarov v 20. stoletju - Kovács, Attila (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
DEMOGRAPHIC TRENDS OF THE PREKMURJE HUNGARIANS IN THE 20TH CENTURY. The article deals with the demographic history of Hungarians in Prekmurje region (Slovenia), and is based on the analysis of the official population censuses in the period from 1910 to 2002, when the number of Hungarians, populating the autochthonous settlement area, decreased by half. In 1910, 14.354 persons with Hungarian as their mother tongue were registered in this area, which makes 90,8% of the entire population of the region. 90 years later, in 2002 however, there were only 6.237 persons with Hungarian as their mother tongue, representing only 49,1% of the registered population in the autochthonous territory of settlement. The decrease of the number of Hungarians in Prekmurje in this period was caused by several factors: emigration - of Hungarian intelligentsia, mostly - to Hungary at the occassion of historical turning points (in 1919 and 1945), casualties in both World Wars, less and less Slovenes and Jews declaring themselves for Hungarians, employment abroad and migrations, immigration of people of non-Hungarian origin into the autochthonous settlement area of Hungarians in Prekmurje, assimilation, etc.
Keywords: narodne manjšine; Prekmurje; Slovenia; Slovenija; Madžari; popisi prebivalstva; migracije; human migration; zaščita manjšin